Hybrid Nanoparticles of Poly (Methyl Methacrylate) and Antimicrobial Quaternary Ammonium Surfactants - Beatriz Ideriha Mathiazzi; Ana Maria Carmona-Ribeiro (MDPI AG, 2020)
Quaternary ammonium surfactants (QACs) are microbicides, whereas poly (acrylates) are biocompatible polymers. Here, the physical and antimicrobial properties of two QACs, cetyl trimethyl ammonium bromide (CTAB) or dioctadecyl dimethyl ammonium bromide (DODAB) in poly (methyl methacrylate) (PMMA) nanoparticles (NPs) are compared to those of QACs alone. Methyl methacrylate (MMA) polymerization using DODAB or CTAB as emulsifiers and initiator azobisisobutyronitrile (AIBN) yielded cationic, nanometric, homodisperse, and stable NPs. NPs' physical and antimicrobial properties were assessed from dynamic light scattering (DLS), scanning electron microscopy, and viability curves of Escherichia coli, Staphylococcus aureus, or Candida albicans determined as log(colony-forming unities counting) over a range of [QACs]. NPs were spherical and homodisperse but activity for free QACs was higher than those for QACs in NPs. Inhibition halos against bacteria and yeast were observed only for free or incorporated CTAB in NPs because PMMA/CTAB NPs controlled the CTAB release. DODAB displayed fungicidal activity against C. albicans since DODAB bilayer disks could penetrate the outer glycoproteins fungus layer. The physical properties and stability of the cationic NPs highlighted their potential to combine with other bioactive molecules for further applications in drug and vaccine delivery.